Confirmation of a Gametophytic Self-Incompatibility in Oryza longistaminata - Lian, Xiaoping; Zhang, Shilai; Huang, Guangfu; Huang, Liyu; Zhang, Jing; Hu, Fengyi (Frontiers in Plant Science, 2021)
Oryza longistaminata, a wild species of African origin, has been reported to exhibit self-incompatibility (SI). However, the genetic pattern of its SI remained unknown. In this study, we conducted self-pollination and reciprocal cross-pollination experiments to verify that O. longistaminata is a strictly self-incompatible species. The staining of pollen with aniline blue following self-pollination revealed that although pollen could germinate on the stigma, the pollen tube was unable to enter the style to complete pollination, thereby resulting in gametophytic self-incompatibility (GSI). LpSDUF247, a S-locus male determinant in the gametophytic SI system of perennial ryegrass, is predicted to encode a DUF247 protein. On the basic of chromosome alignment with LpSDUF247, we identified OlSS1 and OlSS2 as Self-Incompatibility Stamen candidate genes in O. longistaminata. Chromosome segment analysis revealed that the Self-Incompatibility Pistil candidate gene of O. longistaminata (OlSP) is a polymorphic gene located in a region flanking OlSS1. OlSS1 was expressed mainly in the stamens, whereas OlSS2 was expressed in both the stamens and pistils. OlSP was specifically highly expressed in the pistils, as revealed by RT-PCR and qRT-PCR analyses. Collectively, our observations indicate the occurrence of GSI in O. longistaminata and that this process is potentially controlled by OlSS1, OlSS2, and OlSP. These findings provide further insights into the genetic mechanisms underlying self-compatibility in plants.